2022
DOI: 10.1002/jcsm.13055
|View full text |Cite
|
Sign up to set email alerts
|

Role of sarcopenia in the frailty transitions in older adults: a population‐based cohort study

Abstract: Background Frailty and sarcopenia are age-associated syndromes that have been associated with the risk of several adverse events, mainly functional decline and death, that usually coexist. However, the potential role of one of them (sarcopenia) in modulating some of those adverse events associated to the other one (frailty) has not been explored. The aim of this work is to assess the role of sarcopenia within the frailty transitions and mortality in older people. Methods Data from the Toledo Study of Healthy A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…However, transitions are bi-directional, as improvement from prefrail-to-robust and remaining robust has been also shown, although sarcopenia again plays an important yet negative influence. Of note, sarcopenia does not seem to modify the risk of death associated with a poor frailty status, confirming that poor functional status is a robust predictor of outcome [11].…”
Section: Ageing and Body Composition Changesmentioning
confidence: 74%
See 1 more Smart Citation
“…However, transitions are bi-directional, as improvement from prefrail-to-robust and remaining robust has been also shown, although sarcopenia again plays an important yet negative influence. Of note, sarcopenia does not seem to modify the risk of death associated with a poor frailty status, confirming that poor functional status is a robust predictor of outcome [11].…”
Section: Ageing and Body Composition Changesmentioning
confidence: 74%
“…By analysing data from the Toledo Study of Healthy Aging (i.e. a cohort of community-dwelling older adults aged ≥65 years; n = 1538), Álvarez -Bustos et al [11] report that transitions from robustness to prefrailty and frailty were more frequent in sarcopenic than in nonsarcopenic participants (32.37 vs. 15.18%, P ≤ 0.001; 5.76 vs. 1.12%; P ≤ 0.001, respectively) and from prefrailty-to-frailty (12.68 vs. 4.27%; P = 0.0026). However, transitions are bi-directional, as improvement from prefrail-to-robust and remaining robust has been also shown, although sarcopenia again plays an important yet negative influence.…”
Section: Ageing and Body Composition Changesmentioning
confidence: 99%
“…A quantitative or qualitative decrease in skeletal muscle, or sarcopenia, frequently occurs in older adults and increases their risks of functional impairment, compromised mobility, and accidental injuries 29 . A recent study revealed that sarcopenia accelerated frailty progression among the elderly 30 . Aging also exerts negative effects on brain morphology, manifesting as size attenuation, microbleed emergence, and white matter hyperintensity increment.…”
Section: The Origin Of Frailty: Interplay Between Different Pathologiesmentioning
confidence: 99%
“…Furthermore, they are dynamic processes, with the possibility of transitions from lower to higher levels and, more difficult, from higher to lower states in the case of frailty [ 11 , 12 ]. The presence of sarcopenia, on the other hand, also appears to modulate transitions in frailty status [ 13 ]. Regrettably, both syndromes are frequently detected only when one or both are well established and, often after a seemingly minor event, the individual is already suffering a health crisis with significant functional loss and dependency.…”
Section: Introductionmentioning
confidence: 99%